PEDIATRIC AND ADOLESCENT BURN INJURIES IN INDONESIA: A THREE-YEAR REVIEW FROM A TERTIARY BURN CENTER - Talcha Meidheany Putri Wiyono; Lynda Hariani; Nur Aisiyah Widjaja (Universitas Airlangga, 2026)
Highlights: This study fills the gap in epidemiological data on pediatric and adolescent burn injuries in Indonesia, providing baseline evidence for future research and policy-making. The findings emphasize the need for targeted household prevention and nutritional management strategies to improve clinical outcomes in pediatric burns. Abstract: Introduction: Burn injuries are a major cause of morbidity and mortality among children, leading to significant tissue damage, long-term disability, and death. Globally, approximately 180,000 burn-related deaths occur annually, with young children disproportionately affected due to curiosity, immature motor skills, and inadequate supervision. In Indonesia, the incidence of pediatric burns remains high, particularly in domestic settings, yet data from referral hospitals remain limited. This study aimed to describe the clinical profile of pediatric burn patients to inform prevention and treatment strategies. Methods: A retrospective descriptive study was conducted using medical records of 61 pediatric patients aged 0–18 years treated at the Burn Unit of Dr. Soetomo General Academic Hospital, Surabaya, from 2021 to 2023. Total sampling was applied. Variables included age, sex, burn etiology, burn depth, total body surface area (TBSA), and nutritional status. Data were analyzed descriptively. Results: Most patients were male (63.93%) and aged 0–5 years (70.49%). All burns were thermal in origin, predominantly hot water scalds (60.66%). Deep-dermal burns were most frequent (50.82%), and TBSA involvement of 10–20% was common (32.79%). While most patients had normal nutritional status aged 0-5 years (51.16%) and 6-18 years (61.11%), mild to severe malnutrition was observed. Conclusion: Pediatric burns in this center primarily affected boys under five years old, with hot water scalds, deep-dermal injuries, and moderate TBSA involvement predominating. Findings highlight the need for targeted household prevention, timely clinical intervention, and nutritional management to reduce the burden of pediatric burns.